2019
DOI: 10.1038/s41396-019-0564-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community and geochemical analyses of trans-trench sediments for understanding the roles of hadal environments

Abstract: Hadal trench bottom (>6000 m below sea level) sediments harbor higher microbial cell abundance compared with adjacent abyssal plain sediments. This is supported by the accumulation of sedimentary organic matter (OM), facilitated by trench topography. However, the distribution of benthic microbes in different trench systems has not been well explored yet. Here, we carried out small subunit ribosomal RNA gene tag sequencing for 92 sediment subsamples of seven abyssal and seven hadal sediment cores collected from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 110 publications
15
92
0
Order By: Relevance
“…1). These results are similar to previous studies on the microbial composition of hadal trench sediments [26,27], indicating their general signi cance in maintaining the structure and functions of the hadal biosphere.…”
Section: Composition and Activity Of Chloro Exi In Sediments Of The Csupporting
confidence: 91%
See 1 more Smart Citation
“…1). These results are similar to previous studies on the microbial composition of hadal trench sediments [26,27], indicating their general signi cance in maintaining the structure and functions of the hadal biosphere.…”
Section: Composition and Activity Of Chloro Exi In Sediments Of The Csupporting
confidence: 91%
“…However, despite the complex OM supply and extreme environmental conditions, such as high pressure, active microbial carbon turnover in hadal sediments has been frequently reported, making the hadal trenches "hot spots" of OM remineralization in the deep ocean [23][24][25]. Recently, Chloro exi have been identi ed as one of the dominant taxa in seawater and sediment of the hadal trenches [15,26,27], and were found to primarily belonged to novel lineages [27]. In addition, hadal Chloro exi were not only numerically dominant, but also highly transcribed in both hadal seawater and sediments (accounting for up to 36.2% of transcribed prokaryotic 16S rRNA sequences), suggesting a high in-situ activity [15,27].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed two distributional patterns of MG-I subgroups: the ε-ζ-θ subgroups were present across all depth intervals and the η-κ-υ subgroups mainly existed in the MIS 1 stage. The α subgroup may be a mixture of planktonic or benthic MG-I populations ( Figure 6 ), whose presence is likely linked to the availability of oxygen or nitrate in the sediment porewater ( Jorgensen et al, 2012 ; Lauer et al, 2016 ; Hiraoka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Mariana Trench is the deepest known site in the Earth’s oceans, reaching a depth of about 11,000 m at the Challenger Deep. Recent studies revealed that Mariana Trench sediments are enriched in microorganisms [ 10 , 11 , 12 ], however, the structures and bioactivities of their secondary metabolites are poorly known. During the course of our ongoing research program for the discovery of novel bioactive agents from marine microorganisms [ 13 , 14 , 15 , 16 , 17 ], an actinomycete strain SY1965 was isolated from a sediment sample collected from the Mariana Trench at depth of 11,000 m. An extract prepared from the culture of this hadal actinomycete in Gauze’s liquid medium with sea salt showed antiproliferative activities against human glioma U87MG and U251 cells with an inhibition rate of over 100%.…”
Section: Introductionmentioning
confidence: 99%